Preparation method of flame-retardant dynamic cross-linking ABS (Acrylonitrile Butadiene Styrene) polymer
By introducing a dynamic imine bond crosslinking network into ABS polymers, the aldehyde amine condensation reaction of cyclophosphazene crosslinking agents is solved, and the flame retardancy, self-healing and reusability of the material is achieved.
Patent Information
- Application Number
- CN202411757256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ABS plastics are flammable and degraded polymer chains during heat treatment and processing, resulting in performance losses, and thermoset crosslinked bonding materials are difficult to recycle and reuse, which violates the concept of sustainable development.
The amino-modified ABS polymer is subjected to aldehyde-amine condensation reaction with an aldehyde group-containing cyclic phosphazene crosslinking agent to form a dynamic imine bond crosslinking ABS polymer, which imparts flame retardancy, self-healing, repeating processability and recycling properties to the material.
The excellent mechanical properties, flame retardant properties and reusability of the material are achieved, and the flammable and non-reusable problems of traditional ABS materials are solved.
Smart Images

Figure CN119570077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a method for preparing a flame-retardant dynamically cross-linked ABS polymer. Background Art
[0002] ABS plastic is a terpolymer of acrylonitrile-butadiene-styrene, with excellent toughness, rigidity, electrical insulation and other characteristics; at the same time, as a representative of thermoplastic polymer materials, ABS has good processing properties that enable it to be formed through various processing techniques such as molding, injection molding, extrusion, and 3D printing. However, ABS is a flammable material, which is not conducive to practical application, and ABS is often accompanied by polymer chain degradation during repeated heat treatment and processing. The resulting performance loss affects the reuse of ABS. Thermosetting polymers constructed by chemical cross-linking bonds have a stable three-dimensional network structure, showing excellent mechanical properties and dimensional stability, but their insoluble and infusible characteristics make them difficult to recycle and reuse, deviating from the concept of sustainable development.
[0003] The dynamic cross-linking strategy proposed in recent years is an effective way to prepare environmentally friendly recyclable thermosetting polymers. Based on dynamic covalent bonds (such as imine bonds, disulfide bonds, borate bonds, etc.) and non-covalent interactions (such as hydrogen bonds, coordination bonds, host-guest interactions, etc.), researchers have constructed dynamic cross-linking networks with rich types and structures [ACS Macro Letters, 2019, 8 (5): 500-505; Science, 2018, 359 (6371): 72-76; Angewandte Chemie International Edition, 2021, 60 (14): 7947-7955]. Under the stimulation of external conditions (such as light, heat, pH value), the dynamic cross-linking bonds undergo exchange reactions and the cross-linking network is rearranged, thereby giving the material self-healing and reprocessing properties, combining the advantages of both thermoplastic and thermosetting polymers. However, most of the dynamically cross-linked polymers reported so far do not have functional groups and cannot be further endowed with specific functions, which limits the application range of the material. Summary of the invention
[0004] The present invention is to solve the technical problems in the prior art and provide a method for preparing a flame-retardant dynamically cross-linked ABS polymer based on cyclophosphazene. The principle is that an amino-modified ABS polymer and an aldehyde-containing cyclophosphazene cross-linking agent undergo a condensation reaction to form a dynamic cross-linked network in the ABS, thereby improving the mechanical properties of the material while giving the material flame retardancy, self-healing properties, repeatability and recycling properties. The steps of the entire synthesis process are simple, and the raw materials are cheap and easily available. The specific technical scheme is as follows:
[0005] A method for preparing a flame-retardant dynamically cross-linked ABS polymer based on cyclophosphazene comprises the following steps:
[0006] (1) Under the protection of inert gas, ABS is dissolved in an organic solvent, a free radical initiator and a thiol-containing amino modifier are added, and amino groups are introduced into the polymer through a "thiol-ene" click reaction. After the click reaction is completed, the product is precipitated and dried to obtain an amino-modified ABS polymer;
[0007] (2) The amino-modified ABS is dissolved in an organic solvent, and a cyclophosphazene crosslinking agent containing a multi-aldehyde group is added to the reaction system. After being mixed evenly at room temperature, the mixture is poured into a polytetrafluoroethylene mold. After the solvent evaporates to form a film, the mixture is placed in a vacuum oven for further high-temperature curing reaction to obtain a dynamically crosslinked ABS polymer.
[0008] In the above technical solution, the inert gas is preferably nitrogen or argon.
[0009] In the above technical solution, the organic solvent is tetrahydrofuran, dichloromethane, chloroform, dimethyl sulfoxide, dimethylformamide, toluene or chlorobenzene, preferably tetrahydrofuran, dichloromethane or chloroform.
[0010] In the above technical solution, the ABS polymer is obtained by terpolymerization of acrylonitrile, butadiene and styrene, the relative molecular weight of the ABS polymer is 100-1000000 g / mol, the molecular weight distribution of the ABS polymer is 1.0-10, the molar content of acrylonitrile is 10-40%, the molar content of butadiene is 5-50%, and the molar content of styrene is 10%-50%.
[0011] In the above technical scheme, the free radical initiator is an organic peroxide or an azo initiator, wherein the organic peroxide initiator is one or more of dibenzoyl peroxide, dodecyl peroxide, cyclohexanone peroxide, and tert-butyl hydroperoxide, and the azo initiator is one or two of azobisisobutyronitrile and azobisisoheptanenitrile.
[0012] In the above technical solution, the thiol-containing amino modifier is one or more of mercaptoethylamine, mercaptoaniline, 3-mercapto-1-propylamine, 4-mercapto-1-butylamine, and 5-mercapto-1-pentylamine.
[0013] In the above technical solution, the molar ratio of the free radical initiator to the double bonds in ABS is 0.1 to 10, preferably 0.1 to 1;
[0014] In the above technical solution, the molar ratio of the thiol-containing amino modifier to the double bonds in ABS is 0.1 to 10, preferably 1 to 5;
[0015] In the above technical solution, the temperature of the click reaction is 20 to 90° C., and the click reaction time is 1 to 24 hours.
[0016] In the above technical solution, the cyclophosphazene crosslinking agent has the following structure:
[0017]
[0018] Wherein, n is an integer between 3 and 8, preferably 3 or 4;
[0019] R1 is one or more of an aldehyde-substituted C1-C10 aliphatic group, an aldehyde-substituted C1-C10 heteroaliphatic group, an aldehyde-substituted C6-C12 aryl group, and an aldehyde-substituted C1-C12 heteroaryl group;
[0020] R2 is one or more of a substituted or unsubstituted C1-C10 aliphatic group, a substituted or unsubstituted C1-C10 heteroaliphatic group, a substituted or unsubstituted C6-C12 aryl group, or a substituted or unsubstituted C1-C12 heteroaryl group;
[0021] In the above technical solution, the molar ratio of the aldehyde group of the cyclic phosphazene crosslinking agent to the amino group in the aminated ABS is 0.01 to 1, preferably 0.05 to 1;
[0022] In the above technical solution, the temperature of the curing reaction is 90 to 150° C., and the curing reaction time is 1 to 10 hours.
[0023] The beneficial effects of the present invention are:
[0024] The present invention provides a method for preparing a flame-retardant dynamically cross-linked ABS polymer, wherein an amino-modified ABS polymer and an aldehyde-containing cyclic phosphazene cross-linking agent undergo an aldehyde-amine condensation reaction, and the preparation of the dynamically cross-linked ABS polymer can be achieved without an external catalyst, so that the material has excellent mechanical properties, repeated processing properties, and recycling properties. In addition, the introduction of the phosphazene ring gives the ABS polymer phosphorus-nitrogen synergistic flame retardant properties, solving the problems of low flame retardancy, inability to reprocess, and inability to recycle and reuse of traditional cross-linked ABS. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0026] Figure 1 It is the infrared spectra of the dynamically cross-linked polymer prepared in Example 2 of the present invention and the control sample ABS.
[0027] Figure 2 It is a stress-strain curve diagram of the dynamically cross-linked polymers prepared in Examples 1 to 5 of the present invention and the control sample ABS.
[0028] Figure 3 This is a photograph of the dynamic cross-linked polymer prepared in Example 2 of the present invention after repeated processing.
[0029] Figure 4 It is a thermogravimetric curve of the dynamically cross-linked polymer prepared in Example 5 of the present invention and the control sample ABS.
[0030] Figure 5 It is a heat release rate curve diagram of the dynamically cross-linked polymer prepared in Example 5 of the present invention and the control sample ABS. DETAILED DESCRIPTION
[0031] The present invention provides the following examples as further illustrations, but does not limit the scope of protection of the claims of the present invention. The present invention provides a method for preparing a flame retardant dynamically cross-linked ABS polymer, which is achieved by the following steps:
[0032] Firstly, ABS is subjected to a click reaction in a conventional stirred reactor to obtain amino-modified ABS; an aldehyde-containing cyclic phosphazene crosslinking agent is synthesized by reacting chlorinated cyclic phosphazene with sodium salt of phenol containing an aldehyde group; then the crosslinking agent is uniformly mixed with the amino-modified ABS in a solution, and an aldehyde-amine condensation reaction is performed to form an ABS polymer crosslinked by a dynamic imine bond; and the introduction of the cyclic phosphazene gives the material certain flame retardant properties.
[0033] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0034] Example 1
[0035] Under anhydrous and oxygen-free conditions, 50g ABS was dissolved in 500mL tetrahydrofuran, wherein the molar fraction of butadiene was 13.8% and the mass fraction was 9.7%. 20g mercaptoethylamine and 3g azobenzene diisobutyronitrile initiator were added to the reaction bottle, and after stirring and reacting at 60°C for 12 hours, a small amount of ethanol solution was added to terminate the reaction. The reaction solution was then poured into a large amount of ethanol for sedimentation. The obtained polymer was placed in a vacuum drying oven at 40°C and dried for 48 hours to obtain an amino-modified ABS polymer for standby use.
[0036] In a reaction flask, tetrahydrofuran is used as a solvent to react hexachlorocyclotriphosphazene and 4-formylphenol sodium salt to obtain a hexa(4-formylphenoxy)cyclotriphosphazene crosslinking agent for later use.
[0037] Weigh 10 g of the above-mentioned amino-modified ABS polymer, dissolve it in tetrahydrofuran, add 0.12 g of cyclophosphazene crosslinker to the reaction bottle, mix them according to the [-CHO] / [-NH2] molar ratio of 5%, stir and react for 3 hours at room temperature, pour the reaction solution into a polytetrafluoroethylene mold, and after the solvent evaporates to form a film, put it into a 150-degree vacuum oven for further curing reaction for 5 hours to obtain an imine bond crosslinked ABS polymer, marked as ABS-5%. The physical and mechanical properties of the obtained sample are shown in Table 1.
[0038] Example 2
[0039] The experimental conditions are as follows: 10 g of the above-mentioned amino-modified ABS polymer is weighed and dissolved in tetrahydrofuran, and 0.25 g of cyclophosphazene crosslinking agent is added to the reaction bottle, and the mixture is mixed at a [-CHO] / [-NH2] molar ratio of 10%. After stirring and reacting for 3 hours at room temperature, the reaction solution is poured into a polytetrafluoroethylene mold, and after the solvent evaporates to form a film, it is placed in a 150-degree vacuum oven for further curing reaction for 5 hours to obtain an imide bond crosslinked ABS polymer, which is marked as ABS-10%. The physical and mechanical properties of the obtained sample are shown in Table 1.
[0040] Example 3
[0041] The experimental conditions are as follows: 10 g of the above-mentioned amino-modified ABS polymer is weighed and dissolved in tetrahydrofuran, and 0.5 g of cyclophosphazene crosslinking agent is added to the reaction bottle, and the mixture is mixed at a [-CHO] / [-NH2] molar ratio of 20%. After stirring and reacting for 3 hours at room temperature, the reaction solution is poured into a polytetrafluoroethylene mold, and after the solvent evaporates to form a film, it is placed in a 150-degree vacuum oven for further curing reaction for 5 hours to obtain an imide bond crosslinked ABS polymer, which is marked as ABS-20%. The physical and mechanical properties of the obtained sample are shown in Table 1.
[0042] Example 4
[0043] The experimental conditions are as follows: 10 g of the above-mentioned amino-modified ABS polymer is weighed and dissolved in tetrahydrofuran, 1 g of cyclophosphazene crosslinking agent is added to the reaction bottle, and the mixture is mixed at a [-CHO] / [-NH2] molar ratio of 40%. After stirring and reacting for 3 hours at room temperature, the reaction solution is poured into a polytetrafluoroethylene mold. After the solvent evaporates to form a film, it is placed in a 150-degree vacuum oven for further curing reaction for 5 hours to obtain an imide bond crosslinked ABS polymer, which is marked as ABS-40%. The physical and mechanical properties of the obtained sample are shown in Table 1.
[0044] Example 5
[0045] The experimental conditions are as follows: 10 g of the above-mentioned amino-modified ABS polymer is weighed and dissolved in tetrahydrofuran, and 1.5 g of cyclophosphazene crosslinking agent is added to the reaction bottle, and the mixture is mixed at a [-CHO] / [-NH2] molar ratio of 60%. After stirring and reacting for 3 hours at room temperature, the reaction solution is poured into a polytetrafluoroethylene mold, and after the solvent evaporates to form a film, it is placed in a 150-degree vacuum oven for further curing reaction for 5 hours to obtain an imide bond crosslinked ABS polymer, which is marked as ABS-60%. The physical and mechanical properties of the obtained sample are shown in Table 1.
[0046] In order to fully demonstrate the characteristics of the flame-retardant dynamically cross-linked ABS polymers prepared in each embodiment, the obtained samples and the unmodified control sample ABS were analyzed and characterized by the following methods:
[0047] (1) Melting point (T m ) and glass transition temperature (T g ) was measured by TA Instruments Q200.
[0048] Take 5-10 mg of cross-linked polymer sample and heat it to 200℃ at 10℃ / min, keep it constant for 1min to eliminate thermal history, then cool it to 25℃ at 10℃ / min, keep it constant for 1min, and then heat it to 200℃ at 10℃ / min. The T value of the polymer is obtained from the second heating curve. m and T g .
[0049] (2) Tensile properties were tested using a universal testing machine (Instron 5967).
[0050] The testing machine is equipped with a 500N electronic load cell and a mechanical fixture. The test temperature is 25°C and the upper beam movement speed is 50mm / min.
[0051] (3) Thermogravimetric analysis was performed using a TG209F1 Libra thermogravimetric analyzer with a maximum test temperature of 800 °C and a heating rate of 10 °C / min.
[0052] (4) The calorimetric performance test was carried out using a DEATAK MCC-3 micro calorimeter with a maximum test temperature of 700 °C and a heating rate of 1 °C / min.
[0053] Table 1. Test results of ABS control sample and samples of Examples 1 to 5
[0054]
[0055]
[0056] Table 1 shows the relevant test results of the ABS control sample and the samples prepared in Examples 1 to 5. It can be seen that compared with the uncrosslinked ABS polymer in the control sample, the tensile strength of the dynamically crosslinked ABS polymer prepared in Examples 1 to 5 is significantly improved, and the elongation at break shows a trend of first increasing and then decreasing with the increase in the amount of crosslinking agent input. Among them, the polymer prepared according to the experimental conditions of Example 2 has both high strength and high toughness; compared with the residual carbon rate of ABS of only 5.4%, the residual carbon rate of the dynamically crosslinked ABS polymer prepared by the method provided by the present invention can reach more than 20%, and the heat release rate is significantly reduced from 704.7W / g to 559.4W / g, showing a certain flame retardancy.
[0057] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a flame retardant dynamically cross-linked ABS polymer, characterized in that: The following steps are involved: (1) Under the protection of inert gas, ABS is dissolved in an organic solvent, a free radical initiator and a thiol-containing amino modifier are added, and amino groups are introduced into the polymer through a "thiol-ene" click reaction. After the click reaction is completed, the product is precipitated and dried to obtain an amino-modified ABS polymer; (2) The amino-modified ABS is dissolved in an organic solvent, and a cyclophosphazene crosslinking agent containing a multi-aldehyde group is added to the reaction system. After being mixed evenly at room temperature, the mixture is poured into a polytetrafluoroethylene mold. After the solvent evaporates to form a film, the mixture is placed in a vacuum oven for further high-temperature curing reaction to obtain a dynamically crosslinked ABS polymer.
2. The method according to claim 1, characterized in that The inert gas is nitrogen, the organic solvent is tetrahydrofuran, the free radical initiator is azobisisobutyronitrile, and the thiol-containing amino modifier is mercaptoethylamine.
3. The method according to claim 1, characterized in that: The ABS polymer is obtained by terpolymerization of acrylonitrile, butadiene and styrene. The relative molecular weight of the ABS polymer is 100-1000000 g / mol, the molecular weight distribution of the ABS polymer is 1.0-10, the molar content of acrylonitrile is 10-40%, the molar content of butadiene is 5-50%, and the molar content of styrene is 10%-50%.
4. The method according to claim 1, characterized in that: The molar ratio of the free radical initiator to the double bonds in ABS is 0.1-10, and the molar ratio of the thiol-containing amino modifier to the double bonds in ABS is 0.1-10.
5. The method according to claim 1, characterized in that The temperature of the click reaction is 20 to 90° C., and the click reaction time is 1 to 24 hours.
6. The method according to claim 1, characterized in that The cyclophosphazene cross-linking agent has the following structure: Wherein n is an integer between 3 and 8; R1 is a C1-C 10 Aliphatic groups, aldehyde-substituted C1~C 10 Heteroaliphatic groups, aldehyde-substituted C6~C 12 C1~C 12 One or more heteroaryl groups; R2 is substituted or unsubstituted C1~C 10 Aliphatic group, substituted or unsubstituted C1~C 10 Heteroaliphatic group, substituted or unsubstituted C6~C 12 Aryl, substituted or unsubstituted C1~C 12 One or more heteroaryl groups.
7. The method according to claim 1, characterized in that The molar ratio of the aldehyde group in the cyclophosphazene crosslinking agent to the amino group in the aminated ABS is 0.01-1.
8. The method according to claim 1, characterized in that The curing reaction temperature is 90 to 150° C., and the curing reaction time is 1 to 10 hours.
Citation Information
Patent Citations
Method for synthesizing thermo-reversible cross-linking modified elastomeric material based on Schiff base reaction
CN106189040A
Bio-based flame-retardant recyclable polyimide material and preparation method thereof
CN118580448A
Non-linear phosphazene polymer having schiff base structures, process for the preparation thereof, and curable phosphazene composition
US4988791A
Cited By
Halogen-free flame-retardant composite material for cable filling rope and preparation method thereof
CN120623560A